Sistemas intensivos de produção de leite e segurança alimentar : aflatoxinas e resíduos de organofosforados e carbamatos - Navarro, Rodrigo Barros (2011)
In order to measure the contamination by mycotoxins and residues of organophosphates and carbamates and to evaluate the behavior of the milk composition in the Dairy Production Intensive System (DPIS) there was carried out studies from 31 dairy farms in the region of Campos Gerais in the year 2009/2010. Milk samples were analyzed for AFM1 through a competitive ELISA immunoassay kit-Ridascren ® and concentrates analyzed for aflatoxins B1, B2, G1, G2 by the method of thin layer chromatography - CCD. The residues of organophosphates and carbamates in milk and concentrates were determinated by the qualitative colorimetric method. There was contamination of 93.5% of AFM1 in milk samples, but all below the maximum tolerable limit by the Brazilian legislation (0.5 μg.L-1). There was no statistical difference (P>0.05) between seasons (January and July 2010). For organophosphate residues it was observed contamination of 71.0% of the milk samples and 30.7% in concentrates, whereas for carbamate it was observed contamination of 19.4% of the milk samples and 11.7% in concentrates. Adequate measures in the livestock and agriculture management are important to prevent contamination of milk and concentrated feed. To evaluate the behavior of the components of milk in different DPIS it was used official milk recording data from 26 dairy farms and production systems. It was carried out the method of variables selection through the Multiple Correspondence Analysis (MCA) and Analysis of Ascending Hierarchical Classification (AHC), then regression analysis considering the response variables against the covariate lactation number. With the formation of the clusters it was observed the behavior of the milk components, where both milk production and somatic cell count increased with advancing lactation number. The contents of protein, lactose and total solids tended to decrease with the effect the increased milk yield, whereas the fat percentage showed little variation. Regardless of the DPIS, represented by clusters, milk components behaved the same way with increasing lactation number,